A cidade da energia: Tucuruí e uma análise da ocupação da Amazônia através da imprensa nas décadas de 1970 e 1980 - OLIVEIRA, Ana Paula Sanches do Carmo (2025)
This work analyzes the impact of the predatory occupation of the Amazon through journalistic discourses on the construction of the Tucuruí hydroelectric plant. I propose an analysis of the impacts of the military dictatorship's projects from 1964 in Tucuruí and their repercussions through the national and regional press. Although there are already studies on the socio-environmental impacts of the work, this paper focuses on the narratives of the press, which make explicit political, social, and cultural issues, through exogenous and endogenous perspectives. The press was fundamental in constructing the image of the military regime as modern, powerful, and a promoter of development where the State was present and imposing. The Amazon began to be perceived by the Brazilian State, or more precisely, as a target of government actions when its economic and energy potential was recognized, being seen as a “thing” capable of generating enormous profits – in the case of Tucuruí, electricity – and that needed to be “settled” and “civilized.” The idea of a demographic and cultural void encouraged the production of representations of an Amazon that should achieve progress and integration into Brazil.